2009
DOI: 10.1021/nl902842g
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Stacking-Faults-Free Zinc Blende GaAs Nanowires on Si Substrate by Using AlGaAs/GaAs Buffer Layers

Abstract: Vertical GaAs nanowires on Si (111) substrate were grown by metal organic chemical vapor deposition via Au-catalyst vapor-liquid-solid mechanism. Stacking-faults-free zinc blende nanowires were realized by using AlGaAs/GaAs buffer layers and growing under the optimized conditions, that the alloy droplet act as a catalyst rather than an adatom collector and its size and composition would keep stable during growth. The stable droplet contributes to the growth of stacking-faults-free nanowires. Moreover, by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
49
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 28 publications
1
49
0
Order By: Relevance
“…28 In Ref. 29, pure ZB, Gacatalyzed GaAs NWs ͑although containing two twin ZB orientations͒ has been obtained by MBE on the GaAs substrates coated with a sputtered silicon dioxide layer.…”
Section: Introductionmentioning
confidence: 99%
“…28 In Ref. 29, pure ZB, Gacatalyzed GaAs NWs ͑although containing two twin ZB orientations͒ has been obtained by MBE on the GaAs substrates coated with a sputtered silicon dioxide layer.…”
Section: Introductionmentioning
confidence: 99%
“…This area has gained a renewed interest, thanks to the possibility of obtaining defect-free III-V nanowires (NWs) on silicon or even germanium. [3][4][5][6][7][8][9] Although the self-organized growth of III-V NWs on silicon has been intensively studied in the last few years, [10][11][12][13][14] important issues such as those concerning the polarity mismatch between III-V NWs and the group IV substrate remain unsolved.…”
Section: A Introductionmentioning
confidence: 99%
“…Problems include lattice mismatch, thermal expansion coefficient mismatch and formation of anti-phase domains [9]. Recent works have shown that GaAs NWs can be epitaxially grown on Si substrates by controlling the nucleation of NWs through substrate etching [10] or by growing a buffer layer prior to NW growth [2,11]. Others have also shown that a highly effective way of reducing dislocation and relieving strain in the GaAs film on Si is through the use of nanoscale patterned growth [12,13].…”
Section: Introductionmentioning
confidence: 99%